ANALYZING THE RELATIONSHIP BETWEEN LAW AND TECHNOLOGY - Dany Try Hutama Hutabarat; Muhammad Azhari Efendi; Muhammad Fatwa Str; Nanda Prayoga (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2022)
This study aims to find out the relationship between two different field, namely law and information technology, which both aim to improve human welfare. This study employs normative research, which entails evaluating or analyzing secondary data derived from primary, secondary, and tertiary legal materials, which is then assessed descriptively, comparatively, and qualitatively before being encouraged to provide answers to the issues under consideration. Law along with the growth of social life, while information technology exists when the human need for a better life is so important. Thus, the law is needed to control the use of information technology in every side of human life. On the other hand, information technology is needed to help implement the law properly, because of human limitations in collecting and processing so much information. Information technology continues to grow rapidly, expanding into other fields, but this growth is not accompanied by control rules in its application. Generally, in Indonesia laws and regulations regarding the application and use of information technology are slow, and when a law is launched the challenges of legal backwardness are already evident. The legal technology perspective tries to look at things that might be taken into consideration in understanding the possibilities of resolving the lagging laws and regulations compared to the growth of information technology.